ANALISIS KEBERADAAN PG MADUKISMO TERHADAP KESEJAHTERAAN MASYARAKAT DESA TIRTONIRMOLO KABUPATEN BANTUL YOGYAKARTA - Jihan Marha; Zumi Saidah; Pandi Pardian; Rani Andriani Budi Kusumo (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Agroindustry is one sector that expected to improve the economy of the people in a country. The existence of agro-industry will have a positive impact on the surrounding communities. Positive impacts include opening up employment opportunities, opening up new business opportunities and social activities to the community. The purpose of this study was to analyze the relationship between perception of the impact of the existence of PG Madukismo Agroindustry on the welfare of the citizen of Tirtonirmolo Village. This research uses a quantitative approach design and survey techniques in a case. The analysis used is the validity test, reliability test, descriptive analysis, Man Whitney Rank Test (U test), and Spearman Correlation Rank Test. The results of this study indicate that there is a correlation between the perception of the impact of the existence of PG Madukismo Agroindustry on the welfare of Tirtonirmolo Village community.